2021
DOI: 10.1080/17461391.2021.1960426
|View full text |Cite
|
Sign up to set email alerts
|

Exercise in school Physical Education increase bone mineral content and density: Systematic review and meta‐analysis

Abstract: This systematic review and meta-analysis aimed to evaluate the effectiveness of interventions through Physical Education (PE) exercises on bone mineral content (BMC) and density (BMD) of children and adolescents. The research was conducted using the online electronic databases PubMed, Science Direct, Web of Science and Scopus (March 2021). The analysis was restricted to school-based studies that examined the effect of PE interventions on BMC and BMD in schoolchildren (<18 years-old). Standardized mean differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 82 publications
0
11
0
Order By: Relevance
“…Thereby, increasing ASMI through physical activity (i.e., resistance training) would help to increase bone quality through fat reduction ( 62 , 68 , 69 ). This suggestion has practical applicability, as a meta-analysis ( 70 ) that evaluated the effect of interventions with high-intensity physical exercise and sports mini-games at school showed that girls are more responsive to increasing bone mineral density than boys.…”
Section: Discussionmentioning
confidence: 98%
“…Thereby, increasing ASMI through physical activity (i.e., resistance training) would help to increase bone quality through fat reduction ( 62 , 68 , 69 ). This suggestion has practical applicability, as a meta-analysis ( 70 ) that evaluated the effect of interventions with high-intensity physical exercise and sports mini-games at school showed that girls are more responsive to increasing bone mineral density than boys.…”
Section: Discussionmentioning
confidence: 98%
“…The associations between bone mass and physical fitness variables can be based on evidence on the osteogenic effect in childhood of some types of physical exercise ( Rutherford, 1999 ; Vicente-Rodríguez, 2006 ). Different controlled trials in school and non-school settings demonstrate that although the intensity is important, the type of activity also has an important influence on the osteogenic effect ( Tan et al, 2014 ; Larsen et al, 2018 ; García-Hermoso et al, 2021 ; Mello et al, 2021 ). This influence takes place through the actions of the reaction force of the different activities.…”
Section: Discussionmentioning
confidence: 99%
“…The calculation was performed for tests of the F family, considering that the research project foresees association analyses, carried out in another study ( Mello, 2020 ). The alpha used was 0.05, the effect size used was f 2 = 0.15 (moderate) ( Mello et al, 2021 ), and eight variables as predictors. From this protocol, considering the sample size of the present study, the power of the test (1-β) identified was 0.95.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, the systematic reviews by Mello et al (2021) and García-Hermoso et al (2021) demonstrate that interventions with physical exercise and physical activity with vigorous intensity (both with a positive effect on physical fitness) promote gains in bone mass in children and adolescents [e.g., bone mineral content (BMC) and bone mineral density (BMD)]. As Gómez-Bruton et al (2017) have shown that increase in lower limb power through plyometric exercises (effects on muscle power) in children and adolescents causes positive effects on general BMC.…”
Section: Introductionmentioning
confidence: 98%